The Role of the Audit Agency in Maintaining the Integrity of State Budget Use: An Empirical Study of Audit Result Reports - Kurniati, Poni Sukaesih; Suryanto, Suryanto (Jurnal Manajemen Pelayanan Publik, 2025)
The integrity of state budget use is essential for ensuring credible and accountable public financial governance. This study analyzed the role of the Audit Board of Indonesia (BPK) in upholding budget integrity through audits of government financial statements. Using a mixed-method approach, it integrated quantitative analysis of BPK Audit Report data (2018–2023) with qualitative insights from interviews with auditors, policymakers, and academics. The quantitative method applied ordinal logistic regression to examine the impact of audit findings and state losses on audit opinion categories, while the qualitative analysis explored perceptions of BPK’s effectiveness. The findings revealed that a higher number of findings and larger financial losses were negatively associated with audit opinion quality, indicating that audit outcomes reflect actual fiscal integrity. Furthermore, both auditors and policymakers emphasize that BPK's effectiveness depends on institutional independence, the credibility of audit opinions, and the implementation of audit recommendations. These results highlight the requirement to strengthen BPK not only in technical auditing capacity but also in fostering institutional trust and inter-agency collaboration. Accordingly, BPK performs a strategic role in promoting transparency and accountability in public budgeting.